1985
DOI: 10.1128/aem.49.2.443-445.1985
|View full text |Cite
|
Sign up to set email alerts
|

Activated Sludge Biodegradation of 12 Commercial Phthalate Esters

Abstract: The activated sludge biodegradability of 12 commercial phthalate esters was evaluated in two test systems: (i) a semicontinuous activated sludge test and (ii) an acclimated 19-day die-away procedure. Both procedures demonstrated that phthalate esters are rapidly biodegraded under activated sludge conditions when loss of the parent phthalate ester (primary degradation) is measured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…In addition, the increased hydrophobicity of polyesters results in decreased water solubility, indicated by the poor water solubility of POFSI, which can also have a negative impact on enzymatic hydrolysis. Increased water solubility has previously also been mentioned as an important parameter to tune and increase the degradation of phthalic esters [44,45]. Eljertsson et al (1997) concluded that water solubility is a major factor limiting the degradation of hydrophobic phthalic esters by investigating the degradation of phthalic esters under a methanogenic condition.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the increased hydrophobicity of polyesters results in decreased water solubility, indicated by the poor water solubility of POFSI, which can also have a negative impact on enzymatic hydrolysis. Increased water solubility has previously also been mentioned as an important parameter to tune and increase the degradation of phthalic esters [44,45]. Eljertsson et al (1997) concluded that water solubility is a major factor limiting the degradation of hydrophobic phthalic esters by investigating the degradation of phthalic esters under a methanogenic condition.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the polychlorinated biphenyls (42) and 4-nonylphenol (43) bioaccumulate in organisms that are exposed to these chemicals over a period of time, and they also biomagnify through the food chain. However, phthalates appear to be more readily metabolized than these persistent chemicals, particularly by enzymes in the gut (44) and in sewage treatment works, although their rate of degradation does appear to be influenced by the length of their side chains (45,46). It is not known whether the yeast strain employed in the assays shown in this paper is capable of metabolizing complex organic chemicals, although methoxychlor has shown a positive response in the recombinant yeast screen (47); and it has been reported that this chemical must be metabolized before it becomes estrogenically active (48), thus suggesting that the yeast strain is capable of degrading certain organic chemicals.…”
Section: Resultsmentioning
confidence: 99%
“…Low anaerobic degradation rates for other organic compounds like phthalic esters have already been reported. 24,25…”
Section: Anaerobic Degradationmentioning
confidence: 99%